Roles of human development and epidemiological change in the Malaysian health system - Teoh, Hock Geh (2021)
Health financing in mixed health system adopted by Malaysia has faced critical tests of sustainability as a result of progressive changes in political and economic policies toward privatisation, and it is accentuated with the changes of health consumer behaviour along human development progression. The situation is further deepened from rapid demographic and epidemiological transitions which seem not match to the corresponding transition in its health system to better address the current and future needs of its citizens. This study aims to examine the roles of human development and epidemiological change in a sustainable health system. It lays two objectives which both apply Autoregressive Distributed Lag (ARDL) cointegration framework in analysing the time series data from 1997 to 2016. It is set to investigate the effects on private health spending, as unabated expansion of the private health sector has a potential to adversely affect the universal access to care which is congruent to sustainable health system. The first objective of this thesis is aimed to investigate demand factors caused by social change on health expenditures based on influences from human development and fertility transition as a substitute, in addition to epidemiological transitions. The findings reveal private healthcare services has become the preference due to influence of human development and epidemiological transition. In causality test, it also clearly shows health expenditures specifically for private healthcare sector has a supply- induced demand on health consumers to use their services for chronic diseases treatment, and this has caused low fertility rate trend in Malaysia. In comparison of human development factors, human development index (HDI) has shown higher influence as compared to fertility rate on health expenditures. The second objective of this thesis is set to investigate health financing transition from economic changes perspective of existing financing mechanisms. The empirical results based on the bounds testing procedure reveal that Malaysia has rapid and robust health financing transition despite the upward trend on outof- pocket health expenditure share of total health expenditure. The study also reveals that only health financing with pooled financing mechanism would be able to control the out-of-pocket and private health expenditures. Overall, the findings of this thesis are important to the policymakers and health economists in constructing a sustainable health system for upholding social cohesion and welfare. These findings suggest that the government should either improve coverage with options of pooled financing or implement a mandatory universal health financing model to uphold its agenda for universal health coverage. This has become more crucial as the modern societies possess new expectations on health demand as a result from the progress of human development. Thus, it creates an unprecedented phenomenon of inexorable shift towards private healthcare services consumption.